Caracterização genética e fenotípica de amostras do vírus do ectima contagioso - Martins, Mathias (2014)
Orf virus (ORFV) belongs to the family Poxviridae, subfamily Chordopoxvirinae and genus Parapoxvirus and is the agent of contagious ecthyma, a mucocutaneous disease that affects mainly young sheep and goats and, occasionally, may affect people. The clinical lesions progress through stages of hyperemia, papules, vesicles, pustules, ulcers and proliferative and scabby lesions, located mainly on the labial commissure, lips and nostrils. Variable clinical lesions with different degrees of severity often occur in sheep and goats, and may be associated with host and/or viral genetics. The present study aimed to investigate the phenotype in vivo and to characterize virulence genes of four ORFV isolates recovered from contagious ecthyma outbreaks in Rio Grande do Sul State, Brazil. Twenty sheep, aged 6 and 8 months, were divided into five groups of four animals each and inoculated in the labial commissure with homogenates of scabs (viral titers 105.6TCID50/ml) obtained from different outbreaks: SV269/11, SV252/11, SV581/11 and SV820/10-Canguçu. The animals were evaluated for 30 days in clinical and virological aspects by clinical inspection and swab collection for virus isolation. A clinical score was established for each animal and group. All ORFV inoculated animals developed classical ecthyma contagious lesions, characterized by hyperemia, papules, macules, vesicles, pustules and scabs in varied degrees and duration. SV269/10 and SV820/10-Canguçu isolates induced more severe lesions resulting in higher clinical scores and longer duration of lesions. The animals inoculated with SV581/11 developed milder lesions and clinical scores significantly lower than other groups, but they shed virus for a longer period of time. For genetic analyses, PCR amplification and nucleotide sequencing of three virulence genes (VEGF, VIR and IL-10v) were performed. Deletion and mutations on VEGF and IL-10v amino acid sequence of SV581/11 and SV252/11 isolates were identified. The degree of amino acid identity among ORFV sequences was variable, and the lowest homology was found in the VEGF gene of SV581/11 when compared with the standard strains and other viruses. Thus, the present results showed that SV581/11 and SV252/11 isolates, particularly the former, are less virulent in sheep than SV269/11 and SV820/10-Canguçu. Possibly, the variable phenotypic observed in vivo is due to genetic alterations detected in the analyzed virulence genes.